Analisis Peranan dan Manfaat Kemitraan Usaha Singkong Cassesart Antara Koperasi Loh Jinawe dan PT. Cipta Agung Manis di Desa Wunduwatu Kecamatan Andoolo Kabupaten Konawe Selatan - Andriani, Iin; Iswandi, R Marsuki; Abdi, Abdi (Department of Agribusiness, Halu Oleo University, 2018)
This research aims to: 1) analyzing the role of each Cassesart cassava business Partnershipinstitution between the cooperative and PTÂ CAM, and 2) to analyzing the benefits of Cassesart's cassava business partnership for farmers, cooperatives and PT CAM. The population in this research is all Cassesart cassava farmers in Wunduwatu Village, Andoolo District, South Konawe Regency as many as 65 farmers. The number of samples in this study was determined by using slovin formula with error rate of 10%, so that the sample obtained as many as 39 respondents. Selection of respondents is determined based on simple random sampling method (simple random). The results of this research show that cooperative partnership with PT Cipta Agung Manis provide an important role such as procurement of seeds, herbicide and fertilizer for partnership actors and provide benefits for farmers as members of cooperative in technical field such as obtaining guidance in cassava cultivation and increased cassava production. Economis benefits such as marketing of farmersâ€™ products, the companyâ€™s supply of raw material is guaranteed and increasing the income of farmers and for the company can benefit. Social benefits are mutuallybeneficial and create sustainable partnerships